Plasmodium knowlesi malaria in Vietnam: some clarifications - Van den Eede, P.; Vythilingam, I.; Ngo, D.T.; Nguyen, V.H.; Le, X.H.; D'Alessandro, U.; Erhart, A. (2010)
A recently published comment on a report of Plasmodium knowlesi infections in Vietnam states that this may not accurately represent the situation in the study area because the PCR primers used may cross-hybridize with Plasmodium vivax. Nevertheless, P. knowlesi infections have been confirmed by sequencing. In addition, a neighbourjoining tree based on the 18S S-Type SSUrRNA gene shows that the Vietnamese samples clearly cluster with the P. knowlesi isolates identified in Malaysia and are distinct from the corresponding P. vivax sequences. All samples came from asymptomatic individuals who did not consult for fever during the months preceding or following the survey, indicating that asymptomatic P. knowlesi infections occur in this population, although this does not exclude the occurrence of symptomatic cases. Large-scale studies to determine the extent and the epidemiology of P. knowlesi malaria in Vietnam are further needed.